2022
DOI: 10.1080/22221751.2022.2040341
|View full text |Cite
|
Sign up to set email alerts
|

Animal alphacoronaviruses found in human patients with acute respiratory illness in different countries.

Abstract: Here we review the existing evidence of animal alphacoronaviruses ( Alphacoronavirus 1 species ) circulating in human patients with acute respiratory illness. Thus far, the viruses similar to canine, feline and porcine alphacoronaviruses (including the most recent CCoV-HuPn-2018 and HuCCoV_Z19) have been detected in humans in Haiti, Malaysia, Thailand, and USA. The available data suggest that these viruses emerged in different geographic locations independently and have circulated in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…In contrast, only 33%, 48%, and 45% of the PTEs were matched for S, N, and M proteins respectively. Finally, other coronavirus data sets were assembled including 42 other coronaviruses known to infect people, and viruses related to these but sampled in non-human hosts (the beta coronaviruses, MERS, OC43, and HKU1, alphacoronaviruses, NL63, and 229E 24 , plus additional coronaviruses that have recently been associated with human infections 25,26 . These viruses are so distant from sarbecoviruses that reliable alignments for phylogenetic Fig.…”
Section: Development Of Rhad52covconsv Vaccinementioning
confidence: 99%
“…In contrast, only 33%, 48%, and 45% of the PTEs were matched for S, N, and M proteins respectively. Finally, other coronavirus data sets were assembled including 42 other coronaviruses known to infect people, and viruses related to these but sampled in non-human hosts (the beta coronaviruses, MERS, OC43, and HKU1, alphacoronaviruses, NL63, and 229E 24 , plus additional coronaviruses that have recently been associated with human infections 25,26 . These viruses are so distant from sarbecoviruses that reliable alignments for phylogenetic Fig.…”
Section: Development Of Rhad52covconsv Vaccinementioning
confidence: 99%
“…Besides the profound acute severe respiratory syndrome, SCoV2 infection in humans causes gastrointestinal (GI) manifestations (diarrhea, vomiting, nausea, abdominal pain), including longer fecal shedding than those detected in the nasopharyngeal samples [9,65,66]. Both FCoV and CCoV also cause GI tract disease in their respective animal hosts and clinically affect kittens and puppies more than adults, with the exception of FIPV disease [6,23,67].…”
Section: Differential Reactivity To Thementioning
confidence: 99%
“…FCoV2 RBD sequence alignment comparison of CCoV serotype 2 (CCoV2) and FCoV2 RBDs shows 95.6% aa sequence similarity and 87.7% aa sequence identity (S8 Fig) . The high sequence similarity between FCoV2 and CCoV2 RBDs may explain why CCoV2 can infect fAPN expressing feline cells [27]. Although FCoV1 and CCoV1 RBDs possess only aa sequence identity of 55.5%, their sequence similarity of 80.8% is remarkably high (S9 Fig) , suggesting that they have a common lineage with evolutionary changes and perhaps also by sectional recombination [9,29,67].…”
Section: Differential Reactivity To Thementioning
confidence: 99%
See 1 more Smart Citation
“…For example, double homologous recombination of type I FCoV and CCoV gave rise to the emergence of type II FCoV [16]. Notably, recent evidence reported that canine-feline-porcine-like Alpha CoVs have been detected in humans in diferent countries and can be connected with human respiratory illness [17,18]. Abovementioned existing data once again highlight the potential threat of zoonotic CoVs on public health and the importance to conduct surveillance for them.…”
Section: Introductionmentioning
confidence: 99%